Preventing Foodborne Illness: Salmonellosis - Keith R. Schneider; Renée M. Goodrich-Schneider; Michael A. Hubbard; Susanna Richardson (EDIS)
In 2007, there were over 1 million cases and some 400 deaths associated with Salmonella-contaminated food. In 2004, it was estimated that the total economic burden caused by Salmonella infection in the United States was $1.6–$5.3 billion. Food handlers, processors, and retailers can minimize the risk of salmonellosis by using good food handling practices. This 6-page fact sheet was written by Keith R. Schneider, Renée Goodrich Schneider, Michael A. Hubbard, and Susanna Richardson, and published by the UF Department of Food Science and Human Nutrition, March 2013.